Bentuk Tanggung Jawab Perusahaan Serta Perlindungan Hukum Bagi Pekerja Dalam Kasus Perselisihan Pemutusan Hubungan Kerja PT. Tri Jaya Tangguh Kec. Boliyohuto - Husain Mulki Hilala; Weny Almoravid Dungga; Julius T. Mandjo (Jurnal Relasi Publik, 2024)
This research aims to overcome and understand how legal protection is for employees upon termination of employment as well as what factors inhibit the implementation of legal protection for workers' rights due to termination of employment at P.T Trijaya Tangguh District. Boliyohuto, and what the solution is. In this research, the method used is the empirical method, which is a legal research approach that directly evaluates the application of normative legal provisions to specific legal situations that occur in society. The results of this research show that cases of layoffs have occurred at P.T Tri Jaya Tangguh which were caused by many factors. To overcome this problem, it is necessary for labor unions to make more efforts to improve education and provide information to their members about their rights and legal procedures related to layoffs and companies must improve the performance of company management. This can be done by taking steps to periodically evaluate the performance of company leaders, including assessing their ability to build good relationships with subordinates and lead effectively.